New product introduction process improvements in an automotive company - Williams, Omolade Sanu (Cranfield University, 2008)
New product development is an important strategic decision for an automotive company. The need for a structured method of early project planning is herein enforced due to competitive advantage and global market expansion. Client satisfaction constitutes a major challenge that requires the employment of a structured process for turning around a product within a short lead time. To maintain a recognisable and respected position in the market, early and accurate planning and allocation of adequate relevant resources for a successful project is required. A well defined New Product Introduction (NPI) Process will support this concept. It is imperative to ensure that an improved process is aligned to varied project portfolios consistently and integrates seamlessly into the NPI process. Therefore the aim of this study is to enhance the current NPI process within an automotive company and to cover state of the art practice of automotive product development, by accomplishing the following set of objectives: 1. Capture automotive NPI best practice through intensive literature review and industrial applications; 2. Carry out performance measurement survey to identify opportunities of improvement within the current practice of NPI; 3. Propose enhanced NPI process model (addressing the key opportunities for improvement) adapting principles of NPI process best practice; 4. Propose a standardised list of criteria to measure the success of NPI projects; 5. Validate the proposed NPI through expert judgment opinions. The approach adopted in this research is exploratory due to the “how” and “why” questions raised. Supported by comprehensive literature review and supervision, the current NPI process was examined by conducting out a qualitative and quantitative research following a three stage plan. With the use of performance measurementquestionnaire and semi-structured interviews, this thesis sought to respond to three core questions: 1. How applicable is the NPI process? 2. How does Project Management impact the NPI process? 3. What are the areas of opportunities for improvement? The key areas identified, were limited formal procedures, supported by inefficient communication. As a result, this study identified the areas of opportunities for improvement, thereby facilitating the possibility for drivers to successfully implement, adopt and adapt the process.
Keywords: Product Development Process; New Product Introduction; Product Development